2020
DOI: 10.1186/s12967-020-02451-4
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Taiwan Biobank 3.0: vertical and horizontal integration

Abstract: Researchers expect a high quality of biospecimens/data and value-added services from biobanks. Therefore, the concept of "biobank 3.0" was introduced so that biobanks could better meet the needs of stakeholders and maintain sustainable operations. Theoretically, the Taiwan Biobank (TWB) has already gone through the concepts of biobank 1.0 and 2.0. However, three challenges still need to be addressed before it can be transformed into a new generation of the TWB (namely, the TWB 3.0): (1) the difficulty of integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Taiwan has a diverse Chinese ethnic group, thus placing it in a unique position to preserve biological data from different ethnic groups (including aboriginal and Han populations). Integrating and using medical records in the NHI’s database and the genetic profiles of donors in Taiwan’s biobanks is one way of addressing some of the knowledge transition issues associated with precision medicine, and can significantly reduce expenses in this regard [14] . Taiwan’s biobanks and NHI database include billions of images of computed tomography (CT) and magnetic resonance imaging (MRI) scans, as well as their associated data, which can be exchanged with a network of cooperative biobanks globally.…”
Section: Recommendations For Precision Health In Taiwanmentioning
confidence: 99%
See 2 more Smart Citations
“…Taiwan has a diverse Chinese ethnic group, thus placing it in a unique position to preserve biological data from different ethnic groups (including aboriginal and Han populations). Integrating and using medical records in the NHI’s database and the genetic profiles of donors in Taiwan’s biobanks is one way of addressing some of the knowledge transition issues associated with precision medicine, and can significantly reduce expenses in this regard [14] . Taiwan’s biobanks and NHI database include billions of images of computed tomography (CT) and magnetic resonance imaging (MRI) scans, as well as their associated data, which can be exchanged with a network of cooperative biobanks globally.…”
Section: Recommendations For Precision Health In Taiwanmentioning
confidence: 99%
“…In our previous work, Lin et al also reported a framework for how to integrate biobanks vertically and horizontally [14] , so that these institutions can contribute to biological science and share their data widely and globally. Currently, trying to alleviate public concerns regarding privacy infringement, subject to administrative regulations, electronic medical records (EMR) and data from NHI database can be synchronized by and under the supervision of the statistic center of the Ministry of Health and Welfare (MOHW).…”
Section: Recommendations For Precision Health In Taiwanmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects such as return of genetic information derived during research continue to be an issue globally and a topic of intense debate [1][2][3]. Although human GGR can yield information that may be of clinical relevance to the individuals who participate in research, there is not yet a consensus on the responsibilities of researchers to disclose individual research results to research participants [4,5]. In many settings, there is no legal obligations for researchers to return genetic results to participants despite patient willingness to receive the results [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Public biobanks belong to, or operate on behalf of, public institutions, notably university hospitals, and are financed by the state. In general, they can be distinguished between tissue banks of the pathology units of universities and central hospitals and national biobanks such as those in the United Kingdom [5], Taiwan [6], or Estonia [7]. Public biobanks are not for profit and operate in the spirit of public service for research, while private biobanks are primarily composed of collections of samples and data collected by pharmaceutical companies and clinical research organizations and essentially come from clinical studies.…”
Section: Introductionmentioning
confidence: 99%